Investigation on Performance Appraisal System in Bharat Sanchar Nigam Limited (BSNL) - Patel, Chhaya (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
The Performance Appraisal System used by Bharat Sanchar Nigam Limited was investigated. Performance Appraisal helps in creating a positive and healthy climate in the organization. The ability of an organization to precisely measure the performance of its members and use objectivity to optimize them as a valuable resource will therefore be critical to its success. The performance appraisal is critical to the success of any organization. It not only encourages employees, but it also boosts a company's productivity. The project is about the company's Performance Appraisal System and whether or not the employees are happy with it. The employee's data was collected using the questionnaire approach, which was then evaluated and interpreted. The goal of the project is to highlight both the positive and negative aspects of the company's Performance Appraisal System.